Effect of Compost Combination on Methane Emission in Undisturbed Acid Sulphate soil in South Kalimantan of Indonesia - Annisa, Wahida; Maas, Azwar (JOURNAL OF TROPICAL SOILS, 2015)
A greenhouse experiment was conducted to examine the cumulative methane (CH4) emission in paddy soils and correlation with soil redox potential (Eh), soil pH and plant growth. The experiment was arranged in two factorial randomized block designs with three replications. The first factor was a kind of of organic matter, i.e. without organic matter (T0), combination of 50% of composted straws and 50% composted rush weed (T1), combination of 30% of composted straws and 30% composted rush weed and 40% composted cattle manure (T2) and the second factor was the management of water that was continuously flooded and leaching. The methane emission was measured in South Kalimantan using the chamber and gas chromatogram technique. The results showed methane emission in undisturbed acid sulphate soil ranged from 0.05 to 0.32 mg CH4.m-2.minute-1 during the rice-growing season. The methane emission from the paddy soil were lower when the paddy was drained than when it was flooded. Correlation analysis showed a negative relation between methane emission and soil redox potential (Eh) and soil pH in both water management. The rice plant height and number of buds has positively correlation with methane emission with coeffecient correlation of r=0.84**(P<0.0001) and r=0.64**(P=0.004), respectively.Â  [How to Cite: Wahida A and A Maas. 2015. Effect of Compost Combination on Methane Emission in Undisturbed Acid Sulphate soil in South Kalimantan of Indonesia. J Trop Soils 20: 135-141. Doi: 10.5400/jts.2015.20.3.135]Â